Unconventional Photocatalysis in Conductive Polymers: Reversible Modulation of PEDOT:PSS Conductivity by Long-Lived Poly(Heptazine Imide) Radicals - Savateev, Aleksandr; Markushyna, Yevheniia; Schüßlbauer, Christoph; Ullrich, Tobias; Guldi, Dirk Michael; Antonietti, Markus (Angewandte Chemie International Edition, 2021)
In photocatalysis, small organic molecules are converted into desired products using light responsive materials, electromagnetic radiation, and electron mediators. Substitution of low molecular weight reagents with redox active functional materials may increase the utility of photocatalysis beyond organic synthesis and environmental applications. Guided by the general principles of photocatalysis, we design hybrid nanocomposites composed of n-type semiconducting potassium poly(heptazine imide) (K-PHI), and p-type conducting poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) as the redox active substrate. Electrical conductivity of the hybrid nanocomposite, possessing optimal K-PHI content, is reversibly modulated combining a series of external stimuli ranging from visible light under inert conditions and to dark conditions under an O-2 atmosphere. Using a conductive polymer as the redox active substrate allows study of the photocatalytic processes mediated by semiconducting photocatalysts through electrical conductivity measurements.
CRIS-Team WoS Importer:2021-03-19